Analisis Kestabilan Lereng Menggunakan Metode Slope Mass Rating (SMR) dan Software Geoslope/W 2007 pada Tambang Air Laya Selatan Lokasi Suban Di PT Bukit Asam (Persero) Tbk - Nabila Faradibah; Yayuk Apriyanti; Irvani Irvani (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2016)
PT Bukit Asam (Persero) Tbk was one of the Indonesian State Owned Enterprises which conduct tocoal mining. During the process of coal mining, demolition overburden resulted in a change of forceand also set up new structures and caused differences in stress distribution thereby changing thestrength of the rock mass. This result the mining slope becomes unstable and could cause a lot ofharm, therefore the analysis of slope stability was carried out. This study was conducted todetermine the quality of the rock mass slope based on the value SMR (Slope Mass Rating), directionof failure using the analysis of kinematics by Dips software and Safety Factor value (SF) based onMorgenstern Price method using Software Geoslope / W 2007. The data used in this study includesdata UCS, RQD, spacing of discontinuity, discontinuity conditions, groundwater conditions and data ofdiscontinuity orientation. Data retrieval was divided into 9 scanline slopes. The analysis indicatedquality of the rock mass and degree of slope stability based on the SMR for scanline I, VII and IX werevery good with a very stable condition, Scanline II, III, IV, V, VI and VIII had good quality with a steadyslope conditions. The Possibility of slope failure occured only in several blocks for Scanline II, IV, V, VIand VIII. After the analysis of kinematics for Scanline III, IV and V had directions of failure to ScanlineIII was N 490 E, Scanline IV was N 500 E and Scanline V was N 480 E. Values of Safety Factor (SF)single slopes from 9 scanline was estimated to 3.254 - 44.737 (safe condition) and the overall slope of1.85 to 4.09 (safe condition). It was concluded that overall the existing slope on the location Subanwere in a safe condition for SF value >1.25.